HUBUNGAN ANTARA LOCUS OF CONTROL DAN EMOTIONAL QUOTIENT (EQ) DENGAN KELELAHAN KERJA PERAWAT DI RS BHAYANGKARA TK. III MANADO - Pinori, Sara Novi; Kairupan, B.H. Ralph; Rompas, Sefti (Universitas Sam Ratulangi, 2018)
Abstract : Locus of control is a personality trait a person interpreting success and failures experienced by the individual comes from the internal and external factors. Emotional Quotient (EQ) is the capability of a person in understanding and be aware of what had happened either through thoughts, words, and deeds. The purpose of this research is to analyse the relationship between the locus of control and emotional quotient (EQ) and the exhaustion of working nurses. The research design used with Cross Sectional approach. Sampling techniques in research are the total sampling with a sample of 39 respondents. Data were collected using a questionnaire. Based on the results of the test statistic Chi-Square significance level of 95% (É‘ < 0.05) is presented in table 2x2 are obtained for the Locus of control with the fatigue of work p = 0.012 and emotional quotient (EQ) and fatigue of work, p = 0.018, < 0.05. Results of research most respondents experiencing fatigue by using an external locus of control totaled 16 respondents (41%) and experience fatigue with emotional quotient (EQ) low 17 respondents (43.6%). Conclusion there is a relationship between locus of control and emotional quotient (EQ) and the exhaustion of working nurses in RS Bhayangkara TK. III Manado. Keywords: Locus Of Control, Emotional Quotient (EQ), a work Burnout Abstrak : Locus of control adalah suatu sifat kepribadian seseorang dalam menginterpretasikan kesuksesan dan kegagalan yang dialami individu berasal dari faktor internal dan eksternalnya. Emotional Quotient (EQ) adalah suatu kemampuan yang dimiliki seseorang dalam memahami dan menyadari terhadap apa yang dialaminya baik melalui pikiran, perkataan, dan perbuatan. Tujuan dari penelitian ini adalah untuk menganalisis hubungan antara locus of control dan emotional quotient (EQ) dengan kelelahan kerja perawat. Desain penelitian yang digunakan dengan pendekatan Cross Sectional. Teknik sampling dalam penelitian adalah total sampling dengan sampel 39 responden. Data dikumpulkan dengan menggunakan kuesioner. Hasil berdasarkan uji statistik Chi-Square dengan tingkat signifikansi 95% (É‘ < 0,05) disajikan dalam tabel 2x2 yang diperoleh untuk Locus of control dengan kelelahan kerja yakni p = 0,012 dan emotional quotient (EQ) dengan kelelahan kerja yakni p = 0,018, < 0,05. Hasil penelitian sebagian besar responden mengalami kelelahan dengan menggunakan locus of control eksternal berjumlah 16 responden (41%) dan mengalami kelelahan dengan emotional quotient (EQ) rendah 17 responden (43.6%). Kesimpulan ada hubungan antara locus of control dan emotional quotient (EQ) dengan kelelahan kerja perawat di RS Bhayangkara Tk. III Manado. Kata kunci : Locus Of Control, Emotional Quotient (EQ), Kelelahan Kerja